Environmental Taxation and Green Economics in Southeast Asia - Ema Sulisnaningrum; Siti Mutmainah; Eddy Priyanto; Amaury Capdeville Chapuzet (Institute of Research and Community Outreach - Petra Christian University, 2023)
This research aims to simulate models of taxes across Southeast Asia by inserting var models such as environment and gasoline fees. This study is for getting the idea that Southeast Asia imposes an environmental fee based on a regression model derived from Southeast Asia's energy consumption and CO2 emissions adjusted by a 10% additional tax (as a dummy variable). This study was motivated by the European Union's policy suggestions on environmental fees, which could be implemented by Southeast Asia. The log-t methods are used in this study, which allows clustering by countries into additional clubs or convergence groupings, and also for utilizing the test for converging within some panel’s states taking into account the variable’s panel data. We believe that environmental fees are an essential public policy tool in Southeast Asia for reducing CO2 emissions as well as the effects on pollutants. Gas tax or carbon pollution tax upon the energy and transportation industries have a substantial influence on raising tax collections in addition to economic expansion within Southeast Asia. Power tax could help to fund initiatives that utilize ecologically good energy while limiting the prohibiting the utilization of natural gas or eco-friendly power. In the transportation industry, the environmental taxes’ function is to reduce emissions of carbon dioxide caused as a result of less environmentally friendly public transport, as well as to support eco-friendly transport.